2020
DOI: 10.1016/j.xplc.2020.100028
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Efficient Agrobacterium-Mediated Method for Transient Gene Expression and Functional Studies in Multiple Plant Species

Abstract: Although the use of stable transformation technology has led to great insight into gene function, its application in high-throughput studies remains arduous. Agro-infiltration have been widely used in species such as Nicotiana benthamiana for the rapid detection of gene expression and protein interaction analysis, but this technique does not work efficiently in other plant species, including Arabidopsis thaliana . As an efficient high-throughput transient expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 65 publications
1
92
0
Order By: Relevance
“…However, several studies have consistently shown that yeast ADP/ATP carriers are monomeric in structure and function [44]. As the mitochondrial respiratory chain supercomplexes have been investigated by BN-PAGE under different conditions [78], this method could be used to detect the dynamics of the mitochondrial carrier protein complex. In addition, several mitochondrial carriers were also investigated by BN-PAGE, such as the 2-oxoglutarate carrier [52], the dicarboxylate carrier [51], and the tricarboxylate carrier [50].…”
Section: Experimental Evaluation Of the Protein-protein Interactions mentioning
confidence: 99%
“…However, several studies have consistently shown that yeast ADP/ATP carriers are monomeric in structure and function [44]. As the mitochondrial respiratory chain supercomplexes have been investigated by BN-PAGE under different conditions [78], this method could be used to detect the dynamics of the mitochondrial carrier protein complex. In addition, several mitochondrial carriers were also investigated by BN-PAGE, such as the 2-oxoglutarate carrier [52], the dicarboxylate carrier [51], and the tricarboxylate carrier [50].…”
Section: Experimental Evaluation Of the Protein-protein Interactions mentioning
confidence: 99%
“…These results demonstrate that LRBs directly and specifically interact with photoexcited and phosphorylated CRY2. We next examined LRB1-CRY2 and LRB2-CRY2 interactions in vivo, using the BiFC (Bimolecular Fluorescence Complementation) assay in Arabidopsis cells 34 To further test the hypothesis that the Cul3 LRBs and Cul4 COP1-SPAs E3 ubiquitin ligases catalyze blue light-dependent CRY2 ubiquitination, we performed three independent experiments to investigate the activity of LRBs and COP1 in the blue light-induced polyubiquitination of CRY2, using the IP/immunoblot assays. In the first two experiments, we prepared transgenic plants overexpressing Flag-GFP-tagged CRY2 (FGFP-CRY2) in the wild-type (WT), the strong (lrb1lrb2-1lrb3) or weak (lrb1lrb2-2lrb3) alleles of the lrb123 triple mutant ( Fig.…”
Section: Lrbs Interact With Phosphorylated Cry2 To Catalyze Its Polyumentioning
confidence: 99%
“…Western blots were performed as described above. Primary antibodies used here were anti-Flag (1:1500, cat # F1804, Sigma), anti-Myc (1:5000, cat # 05-724, Millipore) and anti-HA (1:5000, cat # 12013819001, Roche), and secondary antibodies used were anti-Mouse-HRP (1:10000, cat # 31430, ThermoFisher) and anti-Rabbit-HRP (1:10000, cat # 31460, ThermoFisher).Bimolecular fluorescence complementation (BiFC) assayBiFC assays in Arabidopsis plants were performed as previously described methods with minor modifications34 . Briefly, Agrobacteria AGL0 transformed with BiFC plasmids were grown in LB medium with 40 μM Acetosyringone and 1% Glucose in 28°C shaker overnight.…”
mentioning
confidence: 99%
“…From the perspective of molecular pharming, lettuce 52,53 serves as a fast-growing crop with a small cultivation footprint in which the edible biomass is also the expressible biomass capable of producing pharmaceuticals. Potato 54,55 represents a slow-growing crop that has the advantage of distinct edible biomass (tubers) and expressible biomass (leaves); molecular pharming would not significantly impact the total available food resource. Leaves detached from the intact plant are capable of providing comparable pharmaceutical yield to those from the intact plant [56][57][58] .…”
Section: A Test Case For Molecular Pharming In Spacementioning
confidence: 99%